Surface Downregulation of Major Histocompatibility Complex Class I, PE-CAM, and ICAM-1 following De Novo Infection of Endothelial Cells with Kaposi's Sarcoma-Associated Herpesvirus - Tomescu, Costin (American Society for Microbiology, 2003)
Under selective pressure from host cytotoxic T lymphocytes, many viruses have evolved to downregulate major histocompatibility complex (MHC) class I and/or T-cell costimulatory molecules from the surface of infected cells. Kaposi's sarcoma-associated herpesvirus (KSHV) encodes two proteins, MIR-1 and MIR-2, that serve this function during lytic replication. In vivo, however, KSHV exists in a predominantly latent state, with less than 5% of infected cells expressing discernible lytic gene products. Thus, mechanisms of immune evasion that depend on genes expressed only during lytic replication are unlikely to be active in most KSHV-infected cells. As a result, we searched for evidence of similar defensive strategies extant during latency, employing culture systems that strongly favor latent KSHV infection. We measured cell surface levels of immunomodulatory proteins on both primary dermal microvascular endothelial cells (pDMVEC) infected through coculture with induced primary effusion lymphoma cells and telomerase-immortalized DMVEC infected directly with cell-free virus. Employing a panel of antibodies against several endothelial cell surface proteins, we show that de novo infection with KSHV leads to the downregulation of MHC class I, CD31 (PE-CAM), and CD54 (ICAM-I) but not CD58 (LFA-3) or CD95 (Fas). Furthermore, flow cytometry with a fluorescently labeled monoclonal antibody to the latency-associated nuclear antigen (LANA) revealed that downregulation occurred predominantly on KSHV-infected (LANA-positive) cells. Although the vast majority of infected cells displayed this downregulation, less than 1% expressed either immediate-early or late lytic proteins detectable by immunofluorescence. Together, these results suggest that downregulation of immunomodulatory proteins on the surface of target cells may represent a constitutive mode of immune evasion employed by KSHV following de novo infection.